Head dislocation after hip joint arthroplasty: modern view (literature review) - Filipenko, Volodymyr; Tankut, Volodymyr; Mezentsev, Volodymyr; Ovchynnikov, Oleh (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Hip arthroplasty is the most effective method for the treatment of severe stages of coxarthrosis, the hip injury and their consequences. The number of hip replacements throughout the world is increasing every year. In Ukraine, such operations are necessary in 150 000 patients per year. Among the complications of hip arthroplasty the most frequent and require repeated surgical procedures are dislocations of the femoral head. During the primary arthroplasty they occur in 0.5–10 % of cases, after revision surgery the risk of their occurrence increases to 10–25 %. Dislocations of femoral head associated with intense pain, a significant deterioration in the functional and mental status of the patient. The article presents the existing classification (for a cause type (mechanism) and time of dislocation), prevention and treatment (conservative and surgical). The main stages of care: emergency, medical and surgical treatments are reviewed. Separately medical tactic is presented for primary and recurrent dislocation of the femoral head. The methods of hip joint fixation after reduction of dislocation and surgical treatment methods (replacement of the head and/or linera implant, revision surgery with complete replacement of the legs and/or cup) are studied. The authors systematized contemporary data about dislocation of the femoral head to determine the main features of classification, prevention and treatment of this complication. It emphasizes the importance of determining the causes of dislocation of the femoral head, preoperative preparation and the choice of optimal tactics of treatment of this disease and its prevention as a basis to prevent the occurrence of dislocation.